Spontaneous CRISPR loci generation in vivo by non-canonical spacer integration - Nivala, Jeff (Nat Microbiol, 2018)
The adaptation phase of CRISPR-Cas immunity depends on the precise integration of short segments of foreign DNA (spacers) into a specific genomic location within the CRISPR locus by the Cas1-Cas2 integration complex. Although off-target spacer integration outside of canonical CRISPR arrays has been described in vitro, no evidence of non-specific integration activity has been found in vivo. Here, we show that non-canonical off-target integrations can occur within bacterial chromosomes at locations that resemble the native CRISPR locus by characterizing hundreds of off-target integration locations within Escherichia coli. Considering whether such promiscuous Cas1-Cas2 activity could have an evolutionary role through the genesis of neo-CRISPR loci, we combed existing CRISPR databases and available genomes for evidence of off-target integration activity. This search uncovered several putative instances of naturally occurring off-target spacer integration events within the genomes of Yersinia pestis and Sulfolobus islandicus. These results are important in understanding alternative routes to CRISPR array genesis and evolution, as well as in the use of spacer acquisition in technological applications.